Methodology to Analyze the Effectiveness of ESD in a Higher Degree in Education. A Case Study - Valderrama-Hernández, Rocío; Sánchez-Carracedo, Fermín; Alcántara Rubio, Lucía; Limón-Domínguez, Dolores (Sustainability, 2020)
This paper presents a methodology to evaluate (1) to what extent students of a higher degree in the field of education acquire sustainability competencies, and (2) to determine whether the subjects that develop Education for Sustainable Development (ESD) achieve their learning objectives. The methodology is applied to a case study. The instruments used are the sustainability survey and the sustainability presence map developed by the EDINSOST project. The survey consists of 18 questions, and has been answered by 104 first-year students and 86 fourth-year students belonging to the Bachelor Degree in Primary Education Teaching at the University of Seville. The Mann-Whitney U test has been used to compare the results of the two students groups, and Cohen’s D has been used to measure the effect size. Students only obtain significant improvements, with 95% confidence, in three questions: Q4 (I know procedures and resources to integrate sustainability in the subjects), Q5 (I analyze the opportunities presented in the subjects to plan educational projects to integrate sustainability) and Q6 (I design educational projects from the perspective of sustainability), all concerning critical thinking and creativity. An improvement is also detected in question Q11 (I know how to develop myself satisfactorily in community educational projects, encouraging participation), with a confidence of 90%. Surprisingly, no subject in the curriculum develops the learning outcomes concerning questions Q4, Q5 and Q6, and only one subject develops the learning outcomes regarding question Q11. However, up to five subjects declare development of the learning outcomes regarding questions in which there is no improvement in student learning. These results suggest that the subjects are failing to reach their ESD learning objectives, and that the students are either trained in sustainability outside the university or the subject learning guides do not reflect the work done by the students throughout their studies.